2004
DOI: 10.1111/j.1442-200x.2004.01838.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of thyroglossal duct cysts in children

Abstract: Misdiagnosis is the most common cause of inadequate and inappropriate surgery, leading to recurrence of the lesion. The authors recommend a Sistrunk procedure for all cases of suspected thyroglossal duct cysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
2
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 15 publications
0
32
2
4
Order By: Relevance
“…Most of the studies reported an equal distribution of TGDCs among males and females [6,11,12]. While Hsieh et al [4] and Turkyilmaz et al [7] observed male and female predominance respectively. In our series, we observed male predominance in both groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies reported an equal distribution of TGDCs among males and females [6,11,12]. While Hsieh et al [4] and Turkyilmaz et al [7] observed male and female predominance respectively. In our series, we observed male predominance in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Schlange then proposed the method of removing mid portion of hyoid bone along with cyst, a procedure that had a recurrence rate of 20% [7]. After the Sistrunk operation introduced in 1920, the recurrence rate reduces to 3-6% [6,12] and it is the standard surgical technique performed for TGDC even today.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore propose that if an incidental TGDC is discovered during surgery, it should be managed in the same manner as a symptomatic TGDC and excised in continuity with the middle third of the hyoid [10][11][12][13][14][15] An exception would be if a Sistrunk procedure would compromise the outcome of the planned surgery. In our small series, a Sistrunk procedure did not negatively impact the outcome of laryngotracheal reconstruction, with all four children being successfully decannulated.…”
Section: Discussionmentioning
confidence: 99%
“…Los defectos del conducto tirogloso se producen por la falta de obliteración del mismo que, normalmente, ocurre en la séptima semana de la vida embrionaria (8).…”
Section: Revisión Del Temaunclassified